Applying Data Envelopment Analysis To Evaluate The Efficiency Of Fishermen Associations In Malaysia - Din, Jamilah (2006)

(untitled)
The fishermen association (FA) in Malaysia has a dual character, as it is both an enterprise and also an association. Hence the business and social performances have to be closely linked. The organization has to perform efficiently to sustain its existence in business and to function as a social organization to its members. With both aspects (economic and social) evaluated equally, it could be categorized as a good or poor performer society. Currently, financial ratios are used to measure the overall financial soundness of the association and the quality of its management. However, due to the association’s dual nature (as it is both an enterprise and also an association) and its multipurpose activities, the overall performance evaluation is often a complicated process. As an alternative form of analysis of the many analytical tools that have been in existence, this study introduces the Data Envelopment Analysis (DEA) method, a non-parametric method to evaluating the performance of the association. Applying DEA to the panel data of 68 FAs from 1994 to 2001, produces estimates of efficiency (the distance of inefficient FAs from the frontier) and the separation of technical efficiency from scale efficiency. Then the measurement of technical progress (the shifting of the best practice over time) allows Malmquist indices of total factor productivity (TFP) to be constructed from the efficiency and technical change measures without recourse to prices. The results are presented as chained indices, so that the rates and causes of TFP growth can be analysed. The Malmquist index is ideal for investigating this problem because it decomposes total factor productivity into technical progress, technical efficiency and scale efficiency measures. Results from this empirical study have identified five “best-practice” FAs, which are located in three different “regions” in Malaysia. The derivation of the Malmquist productivity indices indicated a productivity growth in the socio-economic dimension of 1.033. The economic dimension efficiency showed a productivity growth with a TFP change of 1.015. In contrast, the social performance dimension was marked by a productivity regress with the TFP change score of 0.889. The productivity growth in the socio-economic and economic dimensions had been driven by positive technical change. With respect to the social dimension, the principal cause for the productivity regress was the efficiency change. Overall, the results showed that the FAs needed to improve in their efficiency to catch up with the best-practice frontier as much as by 3.9% in economic performance, 9% in social performance and 3.5% in socio-economic performance. Results indicated that the efficiencies in the economic and social dimensions were determined neither by the length of time in operation and geographical location of the association nor by the amount of grant or subsidy allocated by the government. In conclusion, for the FAs to be efficient with their dual-purpose objective, they need to achieve their optimum productivity in business and provide social benefits for their members, at the same time conforming to the values and practices of cooperative organizations